Correction: Are current guidelines for sun protection optimal for health? Exploring the evidence. Issue 12 (17th July 2018) - Lucas, Robyn M.; Neale, Rachel E.; Madronich, Sasha; McKenzie, Richard L.
Abstract : Correction for 'Are current guidelines for sun protection optimal for health? Exploring the evidence' by Robyn M. Lucas et al., Photochem. Photobiol. Sci., 2018, DOI: 10.1039/c7pp00374a.